International financial shocks in emerging markets - Michael Brei; Almira Buzaushina (University of Bonn, Bonn Graduate School of Economics (BGSE), 2009)
In the present paper, we develop a two-sector general equilibrium model of a small open economy to explore the transmission mechanisms of external financial shocks. In particular, we use a cash-in- advance model with limited participation augmented with a financial friction in the form of a fundamentals-related risk premium on external funds. The friction amplifies the effects of external financial shocks, especially when the economy is highly indebted in foreign currency. For a set of Latin American economies, the theoretical model is calibrated to match the empirical impulse responses of output, investment, trade balance, and domestic credits in response to an adverse shock to the country risk premium. In addition, we analyze the role of monetary policy during the financial crisis.
Keywords: F34; F36; G21; 330; Emerging Markets; Financial Crises; International Capital Markets; Finanzmarktkrise; Schock; Ansteckungseffekt; Länderrisiko; Makroökonomischer Einfluss; Aufstrebende Märkte; Cash-in-Advance-Modell; Internationaler Finanzmarkt; Theorie; Lateinamerika